Testing the impact of personal intelligence on decision-making process for employees of Sudan Academy of Sciences - Mokhtar, Muhand Abbas; Hamid, Adam Ahmed Mousa (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed at testing the impact of personal intelligence on decision-making process for employees of Sudan Academy of Sciences. A questionnaire was designed to collect data from the study population. The SPSS was used for analyzing and testing the hypotheses. Some of the findings of the study are: there is a positive and abstract relationship between personal intelligence and decision-making process and between systematic thinking and decision-making process. The study recommends encouraging employees intelligence in business organizations and suggests conducting further studies for administrative decision makers in business organizations.
Keywords: personal intelligence; decision-making process; motivation; organized thinking